Six Community Psychologists Tell Their Stories : History, Contexts, and Narrative. - Kelly, James G. (Taylor and Francis, 2014)
Six Community Psychologists Tell Their Stories: History, Contexts, and Narrative presents the unique opportunity to examine how culture and social norms have combined with chance, coincidence, and serendipity to form the professional identities of men and women who were among the first generation trained to work in the field of community psychology. The book's contributors?disciples of those who founded the sub-field?provide insights into the factors (social status, family history, education, social environment, cultural events, important ideas) that furthered their professional development in.